The Effectiveness of Active Music Therapy on Anxiety and Sleep Quality in Adolescents Aged 11-14 with Stargardt Disease - Mazloum Vajari, Soheila; Ghasemnegad, Seideh Madineh; Rahimibashar, Masoumeh; Foroughi Kaldareh, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to examine the effectiveness of active music therapy on anxiety and sleep quality in adolescents aged 11-14 with Stargardt disease.Methods and Materials: The current research is a quasi-experimental study with pre-test, post-test, and a control group. In this study, 20 patients with Stargardt disease were selected through convenience sampling and divided into two groups: experimental and control (10 individuals each). They responded to the Spielberger Anxiety Inventory and the Petersburg Sleep Quality Index. Subsequently, training sessions were conducted, followed by post-tests and a one-month follow-up. The research data were analyzed using SPSS software version 22 and the covariance analysis method.Findings: The findings indicated that active music therapy was effective in reducing anxiety and improving sleep quality in adolescents with Stargardt disease (P < 0.01).Conclusion: Music therapy is an affordable, effective, and side-effect-free method that can be introduced for reducing anxiety and improving sleep quality. Health-related centers can utilize it to create better living conditions for such individuals